Diet supplementation with dalbergia palo-escrito hexane extract in fattening rabbits: its effect on productive performance, carcass traits, meat characteristics and meatballs Shelf-Life - Sarai García-Valencia; Sergio Soto-Simental; Juan Ocampo-López; Maricela Ayala-Martínez (Italian Journal of Animal Science, 2022)
This study was conducted to determine the influence of Dalbergia palo-escrito hexane extract supplemented to rabbits on productive performance, blood biochemistry, haematology, carcase traits, meat characteristics and meatballs shelf-life. A hexane extract of D. palo-escrito was obtained from leaves of the tree. Average feed consumption daily gain, average daily weight gain, total weight gain and feed conversion ratio, length body, lumbar circumference, carcase traits, texture profile analysis, meat colour, antioxidant properties, water activity as well as shelf life of meatballs (Total viable bacterial counts, staphylococcus counts, enterobacteria counts, antioxidant activity, pH and water activity) were determined. Feed conversion rate was lower (p < 0.05) in group feed with hexane extract (1.89 and 1.54, for control and hexane extract, respectively). Also, hexane extract decreases feed intake and weight gain. Hot dressing percentage was higher (p < 0.05) in the hexane extract group (48%) than the control group (47%), but the main carcase cuts were similar (p > 0.05) between groups. L* value was lower (p < 0.05) in the hexane extract group (51.2 vs 49.4, for control and hexane extract, respectively). The meatballs prepared with the meat obtained from the hexane extract group showed a lower (p < 0.05) total viable bacterial count after 14 d of storage in refrigeration conditions (8.45 and 4.75 CFU.g−1, for control and hexane extract group, respectively). D. palo-escrito hexane extract decreases productive performance, it is possible that albumin: globulin rate indicates a liver damage, but there no was effect on carcase and meat quality and it increased the shelf life of meatballs.Highlights Extracts of Dalbergia palo-escrito have bioactive compounds Dalbergia palo-escrito could be used to feed rabbits Meatballs increase shelf-life